Metabolome and transcriptome analyses provide new insights into the mechanisms underlying the enhancement of medicinal component content in the roots of Acanthopanax senticosus (Rupr. et Maxim.) Harms through foliar application of zinc fertilizer - Sun, Tongze; Sun, Jialin; Liu, Yuli; Ren, Yanjun; Li, Yifeng; Shi, Chang; Nasr, Alyaa; Tang, Zhonghua; Abozeid, Ann (Frontiers in Genetics, 2023)
Acanthopanax senticosus (Rupr. et Maxim.) Harms is a perennial shrub of the Acanthopanax genus in the Araliaceae family and has a high medicinal value. The application of zinc fertilizer can improve the yield and quality of medicinal materials. However, there are limited reports on approaches to increase the content of medicinal components in A. senticosus, hindering the improvement of its medicinal quality. In this study, A. senticosus was treated with 0.1% (LZn) and 0.4% (HZn) zinc sprayed on the leaf surface. The effects of zinc treatment on the medicinal components in the roots of A. senticosus were analyzed using comprehensive metabolomics and transcriptomics analyses. A total of 316 metabolites were detected, with a prevailing occurrence of terpenoids and phenylpropanoids. We identified metabolites related to the medicinal components that were up-regulated after Zn treatment, including 43 terpenoids, 19 phenylpropanoids, 8 phenols and 3 flavonoids. Combining differential gene expression and K-means analysis, we have found 95, 65 and 25 up-regulated genes related to phenylpropanoid biosynthesis, terpenoid biosynthesis and flavonoid biosynthesis respectively. Under different concentrations of Zn treatment, the up-regulated metabolite biosynthesis-related genes and differentially expressed transcription factors (TFs) varied.Pearson correlation network analysis revealed significant correlations between terpenoids, phenylpropanoids, flavonoids biosynthetic genes and several TFs (ERFs, WRKYs, bHLHs, NACs, MYBs). This study lays the foundation for understanding the metabolic processes in response to varying levels of zinc foliar spray and provides a theoretical basis for enhancing the efficiency of zinc fertilizer utilization in A. senticosus.